Artificial Intelligence Writing Assistants as Reflective Partners: A Quasi-Experimental Study in a Non-English Academic Context - Hikma Tansilo; Yuyun Setiawan Putra; Andini Septama Sari; Tommy Hastomo (Humanitatis : Journal of Language and Literature, 2026)
Argumentative writing is an essential academic skill in higher education; however, students in non-English academic contexts frequently encounter difficulties in developing coherent arguments, organizing ideas logically, and integrating supporting evidence effectively. This study aimed to investigate the effectiveness of Artificial Intelligence Writing Assistants (AIWAs), particularly ChatGPT, in improving Indonesian undergraduate students’ argumentative writing performance. This study employed a mixed-methods approach with a quasi-experimental pretest–posttest control group design. Forty fourth-semester undergraduate students were divided equally into an experimental group receiving AI-assisted feedback through ChatGPT and a control group receiving conventional teacher and peer feedback. Quantitative data were collected through argumentative writing tests and analyzed using paired-samples t-tests, independent-samples t-tests, and gain score analysis. Qualitative data were obtained through classroom observations and semi-structured interviews to provide complementary insights into students’ learning experiences. The results revealed that both groups improved after the intervention; however, the experimental group achieved significantly higher posttest scores (M = 82.70) than the control group (M = 76.90), with a statistically significant difference (p = .005). Qualitative findings further indicated that AIWAs facilitated iterative revision, strengthened coherence and argumentative organization, and enhanced students’ confidence in writing. The findings suggest that AIWAs can serve as effective reflective partners in argumentative writing instruction and offer considerable pedagogical potential to support academic literacy development and digital transformation in higher education, particularly in non-English academic contexts.